MEKANISME PEMILIHAN KEPALA NEGARA DALAM ISLAM DAN HUKUM POSITIF DI INDONESIA - Sutisna (Institut Agama Islam Sahid Bogor, 2022)
The presence of a head of state in the life of the nation and state is a necessity, his presence is expected to be a protector for all citizens. Such is the urgency of a head of state, his presence has become a necessity for all human beings in his various communities. In Islam, the presence of a head of state is expected to be able to carry out the laws of Allah ta'ala and become a protector for all people. While the mechanism for electing heads of state in Indonesia is carried out by direct election by the people to elect candidates for heads of state directly. Prior to the direct election model, in Indonesia the head of state was elected by the People's Representative Council. The DPR itself is elected by the people with a general election mechanism.This research shows that the model of the mechanism for electing a head of state, namely in Islam and in Indonesia, has several similarities in the election process, namely that the election of a head of state is carried out with the agreement of all citizens. They have the right to elect their head of state in the best way possible. If in Islam the election mechanism is not directly regulated, then in Indonesia it is regulated by Law no. 23 of 2003 concerning the election of the president and vice president. The striking difference in this mechanism is that in Islam the election of the head of state is based on Islamic values and must comply with the existing rules, while general elections in Indonesia are based only on democracy, namely power in the hands of the people.